Retrieving the past, recuperating the voice - Reyes, Soledad S.; University of Santo Tomas Publishing House (Manila University of Santo Tomas Publishing House, 2017)
History and criticism on Philippine literature and authors.
Includes bibliographical references (pages 194-201).
English and Tagalog.
Keywords: Philippine literature -- History and criticism; Authors, Filipino -- History -- 20th century